Narratives of identity in social movements, conflicts and change - Hancock, Landon E., 1964- (Research in social movements, conflicts and change ;, 2016)
This volume of Research in Social Movements, Conflicts and Change is divided into two parts. Part I presents a series of cases that tie together narratives of being, knowing and contestation surrounding the claiming of identity for the self or the categorization of the other. It does this by exploring narratives to claim identities and assert agency; showing us the dialectic between dominant forces and those who would challenge existing narratives about place, identity or space. Part II continues RSMCC's tradition of cutting edge research in social movement formation, conflict and change. These chapters focus on a wide range of social organizations from immigrant movements, to the occupy struggle, to the narratives around the framing and counter-framing of the radical environmental movement. The volume concludes with two chapters focusing on more recent developments in data gathering and analysis to examine changes in how researchers collect and analyze data. Each of the nine chapters engages with notions of identity, whether in the examination of the subject or in the reference to the researcher him or herself.